1998
DOI: 10.1044/1058-0360.0702.49
|View full text |Cite
|
Sign up to set email alerts
|

Phonological Assessment and Treatment of Bilingual Speakers

Abstract: Given the demographic changes currently taking place in the United States, speech-language pathologists increasingly are being asked to provide speech and language services to bilingual speakers. The acquisition of more than one language presents unique challenges to speech-language pathologists in the assessment of and intervention for phonological disorders. This paper provides speech-language pathologists information about common and uncommon phonological patterns across a variety of languages, the influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 20 publications
0
22
1
1
Order By: Relevance
“…This finding is contrary to previous studies that have found that bilingual children acquire phonological skills at a slower rate than their monolingual peers (Fabiano-Smith & Goldstein, in press; Yavas & Goldstein, 1998; Gildersleeve, Davis, & Stubbe, 1996). Fabiano-Smith and Goldstein (in press), in a phonological analysis of accuracy of the children in the current study, observed that these same bilingual children demonstrated lower accuracy of production on certain manner classes.…”
Section: Discussioncontrasting
confidence: 99%
“…This finding is contrary to previous studies that have found that bilingual children acquire phonological skills at a slower rate than their monolingual peers (Fabiano-Smith & Goldstein, in press; Yavas & Goldstein, 1998; Gildersleeve, Davis, & Stubbe, 1996). Fabiano-Smith and Goldstein (in press), in a phonological analysis of accuracy of the children in the current study, observed that these same bilingual children demonstrated lower accuracy of production on certain manner classes.…”
Section: Discussioncontrasting
confidence: 99%
“…As Bortolini and Leonard (1991) noted for Italianspeaking children, substitutes across languages may be markedly different. Thus, information in this area may shed light on substitution patterns that might be more (or less) prominent cross-linguistically and help define common/uncommon and typical/ atypical error types as has been done for American English-speaking children (e.g., Smit, 1993a) and as has been suggested for bilingual speakers (Yavaş & Goldstein, 1998). That type of information, which may be useful in making a differential diagnosis and planning intervention, is not available for those delivering services to Spanish-speaking children.…”
mentioning
confidence: 95%
“…Two approaches to bilingual intervention frequently utilized are the bilingual and cross-linguistic approaches. A bilingual approach begins with goals that treat linguistic constructs that are common to both languages or the error patterns exhibited with equal frequency in both languages [23]. The cross-linguistic approach focuses on the linguistic skills that are unique to each language, addressing errors noted in a specific language.…”
Section: Treatment Considerationsmentioning
confidence: 99%
“…The cross-linguistic approach focuses on the linguistic skills that are unique to each language, addressing errors noted in a specific language. Sometimes clinicians, in conjunction with the bilingual approach, to address differences in the linguistic structures of the two languages use this approach [23]. …”
Section: Treatment Considerationsmentioning
confidence: 99%